Macrocyclic malonates. A new family of tethers for the regio- and diastereoselective functionalization of [60]fullerene - Hirsch, Andreas; Chronakis, Nikos (Comptes Rendus Chimie, 2006)
The tether-directed remote functionalization of C has been investigated by using cyclic bis- and trismalonate tethers. The reactive malonate groups are connected with alkyl spacers and their synthesis was performed in one step by the condensation reaction of malonyl dichloride with an appropriate diol. Macrocycles containing identical alkyl spacers afforded bis- and triadducts of C with rotational symmetry in a regioselective manner and in remarkable yields. In contrast, macrocycles bearing different alkyl spacers led to the formation of C-symmetrical bisadducts. Tuning of the spacer's length gave access to different addition patterns of C while, the synthesis of enantiomerically pure trisadducts of C with an e,e,e-addition pattern was achieved via cyclopropanation with chiral D-symmetrical cyclo-tris-malonate tethers. To cite this article: N. Chronakis et A. Hirsch. C. R. Chimie 8 (2005). © 2006 Académie des sciences.